Effect of plant growth retardants on salinity-stress induced changes in sunflower (Helianthus annuus) - SAHA, K; GUPTA, K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1992-93, 1993-94 and 1994-95 to study the effect of plant growthretardans like triazole (LAB 150978 and BAS 111 w) and chlorocholine chlorides in plants of sunflower (HelianthusannuuliS L. cultivar 'EC 68414') grown under 15 and 20 mMho/cm salinity levels of simulated saline soil. Retardants weremade available as soil drench. The plant treated with retardants showed better growth at both the salinity levels but gavebetter yield only under lower salinity level. The retardant-treated plants partially negated the salinity-induced decline inphotosYIlthesis but were unable to alter decline of transpiration or increase of stomatal conductance. Treatment withretardants partially checked the salinity induced increase of Na and CI ion accumulation and also maintained highermetabolic status of leaves.